1999
DOI: 10.1080/096374899101175
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antioxidant activity of milk caseins

Abstract: The antioxidant properties of milk casein subunits (alpha-casein, beta-casein and kappa-casein) were evaluated in liposomal models. All the subunits of casein are able to inhibit Fe-induced peroxidation of arachidonic acid inserted into multilamellar liposomes of dipalmitoylphosphatidylcholine (0.2 mM and 0.8 mM, respectively). The peroxidation was monitored as thiobarbituric acid reactive substances, and the strongest inhibitory effect occurred when 500 micrograms of alpha-casein were added to 0.5 ml of lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Similar results were also reported by Cervato et al (1999) and Zulueta et al (2009), who found that casein fractions of milk were responsible for the majority of the antioxidant capacity. Free radical quenching activity of caseins is due to the oxi dation of aminoacid residues of caseins themselves (Zulueta et al, 2009).…”
Section: Total Antioxidant Capacity Of Deproteinized Milk Samplessupporting
confidence: 79%
“…Similar results were also reported by Cervato et al (1999) and Zulueta et al (2009), who found that casein fractions of milk were responsible for the majority of the antioxidant capacity. Free radical quenching activity of caseins is due to the oxi dation of aminoacid residues of caseins themselves (Zulueta et al, 2009).…”
Section: Total Antioxidant Capacity Of Deproteinized Milk Samplessupporting
confidence: 79%
“…Although the ratio between the single proteomic extract antioxidant ability seems to be close along the three antioxidant tests, the fact that in BTMP performing relatively higher in HS might be related to the Fe 2+ /Fe 3+ cycle interference provoked by casein as reported by Cervato, Cazzola, and Cestaro (1999), making this test less reliable.…”
Section: The Bioactive Components and Antioxidant Activity Of Milk mentioning
confidence: 86%
“…NabM had higher contents of total phenolic content (TPC) and total flavonoid (TF) than PHM ( (Vavrusova et al, 2015) explain it partially; on the other hand, this hydrolysate is composed by single amino acids, modified amino acids (like phosphoserine), or small peptides which are more prone to reaction (exposed groups) than big proteins present in the BTMP mixtures (like casein) which antioxidant and radical-quenching groups are located in the inner motifs (nonexposed groups). Although, according to Cervato, Cazzola, and Cestaro (1999), casein has more antioxidant power than whey proteins like lactoferrin and lactalbumin; it was also proved that the summed antioxidant power of its subunits is higher than of casein as phosphoserine groups become exposed with the subunit's desegregation. Furthermore, Bassan et al (2015) demonstrated a 2.5-fold increase in the antioxidant capacity of whey proteins due to hydrolysis.…”
Section: The Bioactive Components and Antioxidant Activity Of Milk mentioning
confidence: 99%
“…This action of Ksheerabala is also observed in the histopathological studies. The main ingredients of Ksheerabala : Sida cordifolia ,[2 3] milk,[4 5] and sesamum oil[6–14] have all been reported to possess antioxidant properties. The synergistic action of all the components might thus may have potentiated its neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Studies conducted by Korpela et al . [5] have shown that cow's milk had both peroxyl radical-trapping capacity and superoxide radical-trapping capacity.…”
Section: Introductionmentioning
confidence: 99%